2018
DOI: 10.1155/2018/6574731
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Human Immunodeficiency Virus (HIV) and Syphilis in Ghana: A Five-Year Single Urban Site Parallel Population-Based Analysis vis-à-vis the Sentinel Survey

Abstract: The study was aimed at comparing the estimation of the burden and trends (2012–2016) of Human Immunodeficiency Virus (HIV) and Syphilis infections by the national Sentinel Survey vis-à-vis the use of population-based studies at a single urban site (Municipal Hospital) in Ho, the Volta Region of Ghana. Using blood donors as a proxy of the asymptomatic adult population, a retrospective analysis of secondary data on HIV and Syphilis testing was conducted using Ho Municipal Hospital's archives comprising 4,180 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
3
10
2
Order By: Relevance
“…In our previous study, we have observed male preponderance to Treponemal infection [16], and also in the works of Anwar, et al [45]. On the contrary, Coffin, et al [46] and Gao, et al [47], opined that females were more susceptible to Treponemal infection than their male counterparts.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In our previous study, we have observed male preponderance to Treponemal infection [16], and also in the works of Anwar, et al [45]. On the contrary, Coffin, et al [46] and Gao, et al [47], opined that females were more susceptible to Treponemal infection than their male counterparts.…”
Section: Discussionsupporting
confidence: 72%
“…To the best of our knowledge, this is the first comparative study aimed at describing the In general, the cumulative and yearly prevalence of Treponemal infection were significantly higher in the population-based group as compared to that recorded in the Sentinel Survey (p< 0.05), except for year 2017 where the difference was comparable between the two groups (p=0.1416) (Table 1). Thus, our earlier finding of a difference in the rate of Treponemal infections between the two sample groups was not limited to the Ho sentinel site [16], but represents a regional picture. Earlier reports in other African countries also corroborated the results of this study.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Communities in that sub-district lack access to commodities like condoms for prevention of STIs as well as effective health education programmes. In a similar cross-sectional study among antenatal women in Northern Tanzania, syphilis prevalence was found to be higher in rural clinics than those in the urban area [29]. Significant association has been reported between history of coerced sex and syphilis infection in earlier studies.…”
Section: Discussionmentioning
confidence: 97%